The Use of the NHT Type Cooperative Learning Model Can Improve Students' Critical Thinking Ability - Kinasih, Ayang; Mariana, Erni; Yanti, Fitri April; Wardany, Kusuma (Universitas Muhammadiyah Mataram, 2023)
Abstract: Cooperative learning is a learning strategy that involves the active role of students in group collaboration to achieve common goals. Several difficulties were found that caused low student learning outcomes such as the passive atmosphere shown by students in the learning process, this can be seen from the lack of students responding to the questions posed by the teacher, the lack of responsibility of students in doing homework, and there are still students who were not serious during class.This study aims to determine the increase in students' critical thinking skills through the NHT-type cooperative learning model. This research uses Classroom Action Research (CAR), which is a research activity carried out in the classroom as a learning effort, critical reflection on a lesson plan for teacher performance, teacher-student interaction, and student-class interaction. in this study, there was an increase in the number of students who reached the target from cycle I to cycle II. The results in cycle II have reached the set target, this shows that the application of the Use of NHT Type Cooperative Learning Model can improve students' critical thinking skills. This achievement percentage indicates that students experience an increase in critical thinking skills in constructing simple explanations, building basic skills, and concluding. The conclusion of this study is that learning using the Numbered Head Together (NHT) cooperative learning model can improve students' critical thinking skills by up to 34% which can be seen from 3 aspects namely Building Simple Explanations by 31%, Building Basic Skills by 37%, and Concluding 35% in physics class X2 Senior high school.